Identifikasi Isolat Rizobakteri Indigenos Potensial Sebagai Agens Biokontrol Ganoderma boninense - Yanti, Yulmira; Nurbailis, Nurbailis; Rifai, Imam (Jurnal Agro Industri Perkebunan, 2021)
Rhizobacteria is a group of bacteria that colonize roots, affect growth and control plant pathogens. Based on the results of previous studies, 6 isolates have the best ability to control Ganoderma boninense in oil palm seedlings. It is important to characterize them molecularly. Molecular identifications of the selected rhizobacteria isolates were done using the 16S rRNA gene. The results showed that all isolates were identified to have similarity as 5 different species i.e Bacillus paramycoides, Microbacterium paraoxydans, B. albus, B. cereus, and Serratia marcescens based on NCBI database.